LEARNING STYLES OF ECONOMIC STUDENTS UNIVERSITY OF SEMARANG - Metta Christiana; ahmad muhaimin (Universitas Semarang, 2021)
The existence of the corona virus outbreak hampers teaching and learning activities that usually take place face-to-face. The learning system is carried out remotely by utilizing information technology. One of the big challenges in implementing the distance learning model is that the academic community is not yet accustomed to using a blended and online learning system. Teaching lecturers must pay attention to student learning styles because in each teaching, their effectiveness will closely match the student's learning method or style, in addition to their personal characteristics and intellectual abilities. Lecturers' lack of understanding of learning styles has a negative impact on students. The purpose of this study was to examine the learning styles of students of the Faculty of Economics, University of Semarang in a bold manner. This study used a descriptive research design. The population in this study were all 500 USM FE students who took sports courses in the odd semester of 2020/2021, aged 18-25 years. Sampling in this study using total sampling. The data analysis technique in this research is descriptive statistical analysis method. The result of this research is that the learning style of FE USM students has the highest kinesthetic, namely 40.8%, the second is visual as much as 33.8%, the third is auditory as much as 25.4%. Many students prefer an online lecture system by actively viewing, listening and doing direct question and answer with the lecturer, which is 41.2%. The suggestion that can be given is that the lecturers should increase theproportion of teaching the online system with live video, audio, display material and do direct question and answer. Systems with only live audio and display only material should be greatly reduced since few people like them.